Development of Psychology Based on Online with Edward Personality Preference Schedule and High Level Indonesian Collective Intelligence Test - Richard Juan putra Sudarto; Erdhi Widyarto Nugroho; Hendra Prasetya (Journal of Business and Technology, 2021)
Online psychotic are developed to keep up with current technological advancements. Application of Psychotest Development Based on Online with Edward Personality Preference Schedule and High-level Indonesian Collective Intelligence Test, developed for the benefit of the Soegijapranata Center for Applied Psychology. Making the application "Psychotest Development Based on Online with Type of EPPS and High TIKI" is motivated by the director's vision to be able to advance PPT Soegijapranata. In the process of creating an application design, sources were obtained from the director of the Center for Applied Psychology at Uneg Soegijapranata, the design obtained was the number of users, application flow, and mockup design. The goal to be achieved is to change the manual process to use technology. When testing 30 respondents, it was found that the Psychotest Development Application Based Online with EPPS and TIKI Types was quite helpful and made the test process simple.